ChemInform Abstract: Catalytic Asymmetric Cyclopropanation with Diazooxindole. Issue 18 (11th April 2013) - Awata, Atsuko; Arai, Takayoshi
Abstract The use of either 1‐pentene (IIa) or different styrenes affords the heterocyclic scaffold with good to excellent diastereoselectivity, but only moderate enantioselectivity.